The Cognitive Behavioral Treatment of Depression and Low Self‐Esteem in the Context of Pediatric Chronic Fatigue Syndrome (CFS/ME): A Case Study. Issue 4 (16th October 2015) - Loades, Maria
Abstract : Problem: Up to one in three young people with chronic fatigue syndrome (CFS/ME) also has depressive symptoms. It is not known how best to treat young people with this comorbidity. Method: This case report seeks to describe and discuss the use of a cognitive behavioral approach for depression and low self‐esteem in a 16‐year‐old girl with CFS/ME. Findings/Conclusion: Therapy was effective in remediating the young person's mood difficulties, but appeared to exacerbate their CFS/ME symptoms. Therefore, it is crucial that CFS/ME and mood treatments are designed and trialed to ensure a complementary approach. Good communication and joint working between involved professionals is also important, and ideally, treatments for mood and for CFS/ME would be provided by the same team to facilitate this.